Comparison of cognitive performance in bipolar disorder, major depressive disorder, unaffected first‐degree relatives, and healthy controls. Issue 2 (7th December 2018) - Bo, Qijing; Dong, Fang; Li, Xianbin; Li, Feng; Li, Peng; Yu, Haiting; He, Fan; Zhang, Guofu; Wang, Zhimin; Ma, Xin; Wang, Chuanyue
Abstract : Aim: The extent and specifics regarding cognitive dysfunction in patients with bipolar disorder (BD) or major depressive disorder (MDD) and their unaffected first‐degree relatives (FDR) have not been addressed in any single study. The present study compared the cognitive function of patients with BD or MDD, their FDR, and healthy control (HC) individuals. Methods: The study population comprised adults (aged 18–55 years) with BD, adults with MDD, FDR (children or siblings of patients with BD or MDD), and HC ( n = 105, 109, 85, and 95, respectively). The Repeatable Battery for the Assessment of Neuropsychological Status was used to assess neurocognitive functions, with five domains and 12 tests. A Wechsler Adult Intelligence Scale brief form was applied to evaluate IQ. Status of mood was assessed using the Young Mania Rating Scale and the Hamilton Depression Scale. Results: The mixed model indicated significant variation among the four groups in cognitive function. Cognitive impairments, compared to HC, progressively greater from least to most were found in: FDR, MDD, and BD ( F = 32.74, P < 0.001). Years of education correlated with cognitive performance ( F = 17.04, P < 0.001), as did IQ ( F = 240.63, P < 0.001). The total score for the Hamilton Rating Scale for Depression negatively correlated with cognitive function ( F = 5.78, P = 0.017). Conclusion: Among the study groups, patients with BD had the most severe deficits, followed by MDD patients and FDR. Cognitive deficits could not be associated with a specific psychiatric disorder, but differences in degree were noted.